Hepatoprotective bioactivity of the glycoprotein, antrodan, isolated from Antrodia cinnamomea mycelia. - Yaw-Bee Ker; Chiung-Chi Peng; Wan-Lin Chang; Charng-Cherng Chyau; Robert Y Peng (PLoS ONE)
Antrodan, a protein-bound polysaccharide isolated from Antrodia cinnamomea mycelia, was demonstrated to exhibit significant anti-inflammatory bioactivity in vitro. However, its role in hepatic injury in vivo still remains unclear. We hypothesized that antrodan may have beneficial hepatoprotective effects. To verify this, a lipopolysaccharide (LPS)-Sprague-Dawley rat model was used. Antrodan protected against liver damage by suppressing LPS-stimulated serum glutamine-oxaloacetic transaminase (GOT), glutamic-pyruvic transaminase (GPT), interleukin (IL)-6, hepatic thiobarbituric acid reactive substances (TBARS), nitric oxide (NO), inducible NO synthase (iNOS) and nuclear factor (NF)-κB, and by effectively alleviating the downregulated hepatic superoxide dismutase (SOD), catalase, and glutathione peroxidase (GSH-Px). Hematoxylin-eosin staining revealed that antrodan at a dosage of 40 mg/kg was able to alleviate LPS-induced liver damage to a normal status. In addition, we identified the partial main architectural backbone of antrodan to have a 1 → 3 linear β-glycosidic backbone of mannan linked by β-1 → 3 glucosidic branches. Conclusively, antrodan can potentially ameliorate liver damage in vivo by suppressing oxidative stress induced by LPS.